Stedelijk '60 - '70 : : Verzameling 1960 - 1970 : Nederlandse kunst, Buitenlandse kunst. - Welling, Dolf; de Wilde, Edy; van Lerberghe, Jan; Paleis voor Schone Kunsten Brussel (Brussel : La Connaissance, 1971)
Abakanowicz, Magdalena ; Adel, Rolf ; Andersen, Aagaard ; Appel, Karel ; Arman ; Armando ; Awazu, Kiyoshi ; Baarspul, Adriana ; Bakker, Gijs ; Beeke, Anthon ; Bellmer, Hans ; Beltran, Felix ; Bons, Jan ; Boxem, Hilbert ; Brands, Eugène ; Bureau Variksen ; Bureau Varis ; Bury, Pol ; Cage, John ; Cassée, Dick ; Castellani, Enrico ; Castro, Lourdes ; Christo ; Cieslewicz, Roman ; Colombo, Joe ; Constant ; Coper, Hans ; Copier, A.D. ; Corneille ; Courtin, Pierre ; Couzijn, Wessel ; Crouwel, Wim ; Culot, Pierre ; Dado ; Dekkers, Ad ; Dibbets, Jan ; Diederen, Jef ; Dine, Jim ; Dubuffet, Jean ; Van den Eerenbeemt, Gérard L.G.M. ; Elffers, Dick ; van Elk, Ger ; Engels, Pieter ; Escher, Gielijn ; Riverhead (New York) ; Fontana, Lucio ; Freudenreich, Marek ; Gachnang, Johannes ; Geraerdts, Pieter Jr. ; Giles, Maggi ; Van Goethem, Jan ; van Golden, Daan ; Gommans, Huub ; Grygar, Milan ; Heesen, Walter ; Henneman, Jeroen ; Heyboer, Anton ; van der Heyden, Léon ; Hockney, David ; Holdenowicz, Leszek ; Holstein, Pieter ; Huig, Henk ; Huismans, Sipke ; Indiana, Robert ; Jacobsen, Arne ; Johns, Jasper ; Jones, Allen ; De Jong, Hans ; Kaplan, Zdenek ; Keizer, Jerry ; Kelly, Ellsworth ; Kho Liang le ; Kitaj, R.B. ; Klein, Yves ; de Kooning, Willem ; Kracht, Yvonne ; Kramer, Friso ; Krushenick, Nicholas ; Kudo, Tetsumi ; Laitinen, R. ; Lataster, Ger ; van Leersum, Emmy ; Lenica, Jan ; LeWitt, Sol ; Lichtenstein, Roy ; van Loon, Johan ; Louis, Morris ; Lucassen ; Lucebert ; Luginbühl, Bernhard ; Makowski, Zbigniew ; Manzoni, Piero ; Martnez, Raul ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Mayer, Hans-Jörg ; Meijdam, Floris ; Merz, Mario ; Michaux, Henri ; Mon, Franz ; Müller, Robert ; Nauman, Bruce ; Newman, Barnett ; van den Nieuwelaar, Aldo ; Nikifor, Mattei ; etc.
2 ex. : ned. + frans
Frans
Nederlands
Stedelijk '60 - '70 : Verzameling 1960 - 1970 : Nederlandse kunst, 22.9 - 17.10.1971 / Buitenlandse kunst, 20.10 - 22.11.1971, Paleis voor Schone Kunsten Brussel
boek
Keywords: Nederland